RISKS IN THE IMPLEMENTATION OF SMART TECHNOLOGIES IN URBANENVIRONMENTS - Chipriyanov, Mihail (E-Journal VFU, 2025)
Within the scope of the present study, a comprehensive and critical analysis is conducted on the main risks arising from the implementation of smart technologies in urban environments, focusing on challenges to cybersecurity, financial sustainability, social adaptation, and regulatory adequacy. Key issues identified include the vulnerability of IoT devices, the financial burden of implementation, the digital divide, and the lack of unified legal frameworks. As a result of the analysis, specific strategies for minimizing these risks are 935 formulated, encompassing public-private partnerships, financial innovations, enhancement of digital literacy, and the creation of adaptive regulatory approaches. The conclusion drawn is that the successful development of smart cities is directly dependent on the holistic management of these multifaceted risks.